The Effect of Supination and Pronation on Wrist Range of Motion - Kane, Patrick M.; Vopat, Bryan G.; Got, Christopher; Mansuripur, Kaveh; Akelman, Edward (Journal of Wrist Surgery, 2014)
Wrist range of motion (ROM) is a combination of complex osseous articulations and intricate soft tissue constraints. It has been proposed that forearm rotation contributes significantly to carpal kinematics. However, no studies have investigated whether supination or pronation influence this course of motion. The purpose of this study is to examine whether supination and pronation affect the mechanical axis of the wrist. After being screened for gross anatomic abnormalities, six upper extremity cadaver specimens (three matched pairs) were fixed to a custom-designed jig that allows 24 different directions of wrist motion. Each specimen was tested in three separate forearm positions: neutral, full supination, and full pronation. Moments of ± 2 Nm were applied, and the applied moment versus wrist rotation data were recorded. Forearm position did not significantly (p > 0.31) affect the ROM values of the wrist. In forearm neutral, supination, and pronation positions the envelope of wrist ROM values was ellipsoidal in shape, consistent with prior neutral forearm biomechanical testing. The major axis of the ellipse was oriented in a radial extension to ulnar flexion direction, with the largest ROM in ulnar flexion. We hypothesized that forearm position would influence wrist ROM. However, our biomechanical testing showed no statistically significant difference in the orientation of the mechanical axis nor the passive ROM of the wrist. The primary passive mechanical axis in all three forearm positions tested (neutral, supination, and pronation) was aligned with radial extension and ulnar flexion. Although it has been shown that forearm position affects various radioulnar, radiocarpal, and ulnocarpal ligamentous tensions and lengths, it appears that wrist ROM is independent of forearm position. Consequently we feel our biomechanical testing illustrates that wrist ROM is primarily dependent on the osseous articulations of the carpus. Additionally, given that no change is observed in wrist ROM relative to forearm position, the significance of the contribution of the distal radioulnar joint (DRUJ) to wrist kinematics is debatable.
Keywords: supination/pronation; wrist kinematics